Geospatial analysis in monitoring land use encroahment into heritage site in Bujang Valley - Mastor, Intan Siti Zulaikha; Hj. Mohd. Noor, Norzailawati; Abdullah, Muhammad Faris; Abdullah, Alias (IIUM Press, 2014)
This paper attempted at studying the applications of GIS and satellite remote sensing as a land use planning tool in monitoring a development expansion surrounding heritage area in Bujang Valley, Kedah. This research identified the development expansion around the heritage sites in determining a specific boundaries for heritage site in the context of land use planning. The analysis of catchment area for heritage sites has been identified by using GIS and satellite image of SPOT 5.The analysis of development pattern was obtained from temporal images of SPOT 5 using images and layering techniques which have been tested in Bujang Valley, Kedah. The results showed that there were prominent changes in the study area throughout the 11 year period (2004-2012). Supervised land classification analysis showed significant changes of land covers of forest, agriculture and built-up area. Overall, forest land was converted to agriculture and built-up areas while in some localities agriculture land was converted into built-up areas especially in the surrounding areas of the heritage sites. This study showed there was greater value in terms of archaeology and anthropology in handling the issues of urbanization. Simultaneously it presented the analysis of remote sensing and GIS technology which have provided a new direction in handling this issues globally.